A note on marginalisation as an alternative approach in the study of poverty of the Orang Asli Communities in Peninsular Malaysia - Mohd Fauzi Mohd Harun,; Nor Aini Hj Idris,; Gani Osman, A. (Penerbit Universiti Kebangsaan Malaysia, 2009)
Poverty among the Orang Asli is still aseriousproblem. The 1999 Poverty Rate puts the rate for this group at 50.9 % and the hardcore poverty rate at 15.4 %. Research done before this relates poverty to the attitude and the cultural problems of these people. This group of people was said to be lazy, lack discipline, having no enthusiasm to progress and being complacent with their life. Further more, they were also found to be exploited by middlemen. These two approaches to explain poverty of the Orang Asli, are however; no longer suitable. Firstly, if we still insist to blame attitude for the poverty of the Orang Asli, the government would be less enthusiastic in their efforts to develop these people. Next, the exploitative activities of the middlemen have greatly been stifled by the Jabatan Hal Ehwal Orang Asli. This paper intends to reveal the existence of other factors which would be more significant to explain poverty among these indigenous people. The factor is the marginalisation of these people. This refers to the lack of enthusiasm on the part of the authorities in helping the Orang Asli. This happens not only economically but also in the other aspects of fhese indigenous people's life.